Oxidation of lignin-carbohydrate complex by laccase/Co(salen) one-pot catalysis - Zhou, Xue-Fei (Penerbit Universiti Kebangsaan Malaysia, 2022)
Lignin-carbohydrate complex (LCC) is hybrid structures containing covalently linked moieties of lignin and carbohydrates. The nature and amount of LCC affect both industrial processes and practical applications of lignocellulosic biomass. Herein, the LCC was isolated from bamboo by successive solvent extraction and precipitation. The effects and mechanism of LCC oxidation respectively by laccase, Co(salen), and laccase/Co(salen) in the presence of molecular oxygen have been investigated by composition analysis using the standard of National Renewable Energy Laboratory (NREL) and high-performance anion exchange chromatography (HPAEC), GPC, FTIR, and 2D-HSQC NMR. We can conclude that the laccase/Co(salen) one-pot catalysis modified the LCC in such a way that more carbohydrate was removed from the LCC with lower molecular weight of LCC as shown by GPC; the catalytic treatments produced oxidation at lignin side-chains and cleavage of lignin β-O-4’, β-β’ and β-5’ bonds in LCC, and cleavage of benzyl-sugar ether, phenyl glycoside and γ-ester bonds in LCC, as shown by FTIR and 2D-HSQC NMR, especially after the laccase/Co(salen) one-pot treatment. The further insight of LCC degradation was discussed in light of the results obtained in oxidation of the LCC model compound coniferin.